Enhanced biofuel production by co-pyrolysis of distiller's grains and waste plastics: a quantitative appraisal of kinetic behaviors and product characteristics - Li, Gang; Yang, Tenglun; Xiao, Wenbo; Yao, Xiaolong; Su, Meng; Pan, Minmin; Wang, Xiqing; Lyu, Tao (Elsevier, 2023)
Pyrolysis of biomass feedstocks can produce valuable biofuel, however, the final products may present excessive corrosion and poor stability due to the lack of hydrogen content. Co-pyrolysis with hydrogen-rich substances such as waste plastics may compensate for these shortcomings. In this study, the co-pyrolysis of a common biomass, i.e. distiller's grains (DG), and waste polypropylene plastic (PP) were investigated towards increasing the quantity and quality of the production of biofuel. Results from the thermogravimetric analyses showed that the reaction interval of individual pyrolysis of DG and PP was 124–471 °C and 260–461 °C, respectively. Conversely, an interaction effect between DG and PP was observed during co-pyrolysis, resulting in a slower rate of weight loss, a longer temperature range for the pyrolysis reaction, and an increase in the temperature difference between the evolution of products. Likewise, the Coats-Redfern model showed that the activation energies of DG, PP and an equal mixture of both were 42.90, 130.27 and 47.74 kJ mol−1, respectively. It thus follows that co-pyrolysis of DG and PP can effectively reduce the activation energy of the reaction system and promote the degree of pyrolysis. Synergistic effects essentially promoted the free radical reaction of the PP during co-pyrolysis, thereby reducing the activation energy of the process. Moreover, due to this synergistic effect in the co-pyrolysis of DG and PP, the ratio of elements was effectively optimized, especially the content of oxygen-containing species was reduced, and the hydrocarbon content of products was increased. These results will not only advance our understanding of the characteristics of co-pyrolysis of DG and PP, but will also support further research toward improving an efficient co-pyrolysis reactor system and the pyrolysis process itself.
Keywords: Waste recovery; Co-pyrolysis; Distiller's grains; Polypropene; Activation energy; Synergistic mechanism